A thematic analysis of teachers’ experience in teaching inclusive physical education - Agus Sumhendartin Suryobroto; Caly Setiawan; Udon Nampai; Agus Susworo Dwi Marhaendro (Jurnal Cakrawala Pendidikan, 2022)
The current research aimed at investigating physical education teachers’ experiences in practicing inclusive physical education and the meaning they attached to those experiences. The study focused on the thematic analysis of participants’ experiences represented in the collected qualitative data. A number of 12 physical education teachers participated in in-depth interviews and photo elicitation interviews. Verbatim transcripts were obtained from all interviews for subsequent analysis. Using the tenets of thematic analysis (Braun Clarke, 2006, 2019, 2021), analysis included familiarization with the data, open coding, theme construction, theme review, theme naming, and report production. The analysis process yielded four themes of teachers’ experiences including (1) the roles of background knowledge and skills, (2) teaching various types of disabilities, (3) inclusive pedagogy approaches, (3) facilitators and barriers to teaching inclusive physical education. The meaning of the experiences were the meaning of inclusion, inclusive physical education, and inclusive physical education teaching. We conclude that experience is important in delivering inclusive PE, especially with regard to teachers’ development in the area of pedagogical knowledge and skills as well as dealing with challenges in their teaching approaches. Along with this experience is the meaning of teaching inclusive PE which reflected in-depth engagement with this caring profession.